Tribal Society and Deprivations of the Girl Child: A Study in Andhra Pradesh - Murty, C.S. & Subrahmanyam, S. (2005)
The fact that basic health and education facilities are still not within the easy reach of tribal children can hardly be contested and is disturbing. The paper’s conclusion, based on data collected from a sample of 6081 tribal households in four north coastal districts of A.P., covering the year 2002-03, that the tribals rarely defy their culture and tradition to give the benefit of facilities equally to their male and female children makes one even more disquiet. The girl child is particularly discriminated against when a modicum of financial commitment is involved in putting the child out of illiteracy and ill health. An approach that exposes the adult members to the nuances of education appears to mitigate the discrimination meted out to the child, for it makes them better appreciate the value of building the capabilities of the child.